Nuevos retos y perspectivas del puerto de Matarani en el contexto regional en el marco de la globalización - Fernández Ibarra, Elder Junior (2013)
The permanent and each time fastest scientific innovations, as well as technological and telecommunications in the industrialized countries, irreversible influence the productive patterns of the underdeveloped countries. This pushes them to insert themselves and to include withinthis new world order that brings the globalization. These changes are dramatic in countries like ours, whose productive structure is still traditional. The transformation of these structurescomes together with the increment of social inequalities and therefore territorial expressed in hierarchies. However, this will depend on the adaptability capacity of each social group to the new economic context.Peru is not foreign to this type of harbor system that generates a series of dynamics in the role of harbor cities, enhancing them as spatial logistics at global level, where the public and private enterprises’ intervention, as well as the role of the State as local and regional subsidiary agent. These dynamics that result from the network system, the spatial configuration patterns and production of these traditional spaces, and the changes that may occur when insert themselves to a more sophisticated stage than the actual one, is focus of economic development understood as the bettering of the peoples quality of life, are the elements for this research.